Pengaruh Teknik Akrostik Terhadap Keterampilan Menulis Puisi Siswa Kelas V SD Islam Al Amanah Tangerang Selatan - Wafiqni, Nafia; Rosdiani, Aida (PD PGMI se Indonesia, 2019)
The Purpose of the study is to know Influence of Acrostic Technique to Poetry Writing Skills of Students. It was conducted at Al Amanah Islamic Elementary School South Tangerang, 5th grade semester 2015/2016. The method used in this study was quasi-experiment with Non-Equivalent Control Grup Design. Samples were taken by purposive sampling. The first samples included 36 students of experimental class using acrostic technique and 34 students of control class using conventional learning. Based on posttest score, average poetry writing skill of experiment class students who using acrostic technique was higher than average poetry writing skill of controll class students who using conventional learning method. The average pretest score of experiment class was 64,28, while of the control class was 61,21. On the other side, the averafe posttest scored of experiment class was74,89 and the control class was 70,00. Hipothesis two class calculation using T-tes, Paired Sample T Test, achived the significance level of 0,050 showing that probability value (significance) was 0,004. Due to significance of 0,004 < Î± = 0,050, H0 was rejected. This proved that usage of Acrostic Technique Influence to Poetry Writing Skills of Students 5thÂ Grade second semester at Al Amanah Islamic Elementary School South Tangerang 2015/2016.